Anxiety reactions of ELF students toward in-class activities and instructors' personal characteristics and behavior - Rodriguez, Máximo (Lenguas Modernas, 2017)
This study examined the anxiety reactions of EFL students toward in class activities and instructors' personal characteristics and behaviors. No statistically significant difference between the groups of students was found regarding their perceptions of anxiety as generated by the activities. However statistically signifrcant differences in the amount of anxiety perceived by students were found between activities that demanded oral performance in front of the class and small group work activities or activities that did not demand high student self-exposure. Students reported that their English teachers lessened their language anxiety by preparing the classes well, and by establishing a warm social environment in the classroom. Finally students commented that they felt that their language anxiety increased when their instructors created a threatening atmosphere in the classroom.